Fluctuation of Credit Risk and Company Size on Liquidity - Gunardi Gunardi; Akhmad Najibul Khairi Syai; Kholdorov Sardor Umarovich; Muhammad Al Mighwar; Euis Bandawaty; Dewi Kartikaningsih (Fakultas Ekonomi dan Bisnis Islam, 2024)
This study aims to provide empirical evidence on the effect of credit risk and company size on liquidity in the banking sector. Liquidity is an important aspect in assessing a bank's financial performance because it reflects the institution's ability to meet short-term obligations and maintain operational continuity. This study focuses on Bank Mandiri, which consistently shows liquidity stability during the 2013–2023 period, even amidst various economic conditions. The research approach used is quantitative with a time series regression model. Secondary data is obtained from Bank Mandiri's audited annual financial statements. The dependent variable, namely liquidity, is measured using the Loan to Deposit Ratio (LDR); while the independent variables are credit risk measured by the Non-Performing Loan (NPL) ratio, and company size measured by the natural logarithm of total assets. To ensure the validity of the model, classical assumption tests such as normality, multicollinearity, heteroscedasticity, and autocorrelation are carried out. The results of the study show that credit risk and company size have a positive and significant effect on liquidity, both partially and simultaneously. This finding indicates that increasing credit risk encourages banks to strengthen liquidity reserves, and large-scale companies have wider access to funding. This result differs from several previous studies, indicating that institutional characteristics and risk management strategies can affect the direction and strength of the relationship between variables. This study contributes to the literature by presenting time-series evidence on the determinants of liquidity at one of the largest state-owned banks in Indonesia.